1-h Glucose During Oral Glucose Tolerance Test Predicts Hyperglycemia Relapse-Free Survival in Obese Black Patients With Hyperglycemic Crises - Jagannathan, Ram; Stefanovski, Darko; Smiley, Dawn D.; Oladejo, Omolade; Cotten, Lucia F.; Umpierrez, Guillermo; Vellanki, Priyathama (Frontiers in Endocrinology, 2022)
Objective: Approximately 50% of obese Black patients with unprovoked diabetic ketoacidosis (DKA) or severe hyperglycemia (SH) at new-onset diabetes achieve near-normoglycemia remission with intensive insulin treatment. Despite the initial near-normoglycemia remission, most DKA/SH individuals develop hyperglycemia relapse after insulin discontinuation. Traditional biomarkers such as normal glucose tolerance at the time of remission were not predictive of hyperglycemia relapse. We tested whether 1-hour post glucose (1-h PG) at remission predicts hyperglycemia relapse in Blacks with DKA/SH. Methods: Secondary analysis of two prospective randomized controlled trials in 73 patients with DKA/SH at the safety net hospital with a median follow-up of 408 days. Patients with DKA/SH underwent a 5-point, 2-hour 75-gram oral glucose tolerance test after hyperglycemia remission. Hyperglycemia relapse as defined by fasting blood glucose (FBG)>130 mg/dl, random BG>180 mg/dl, or HbA1c>7%. Results. During the median 408 (interquartile range: 110-602) days of follow-up, hyperglycemia relapse occurred in 28 (38.4%) participants. One-h PG value ≥199 mg/dl discriminate hyperglycemia relapse (sensitivity:64%; specificity:71%). Elevated levels of 1-h PG (≥199 mg/dl) were independently associated with hyperglycemia relapse (adjusted hazard ratio: 2.40 [95%CI:1.04,5.56]). In multivariable model with FBG, adding 1-h PG level enhanced the prediction of hyperglycemia relapse, with significant improvements in C-index (Δ:+0.05;P=0.04), net reclassification improvement (NRI: 48.7%;P=0.04), integrated discrimination index (IDI:7.8%;P=0.02) than the addition of 2-h PG (NRI: 20.2%; P=0.42; IDI:1.32%;P=0.41) or HbA1c (NRI:35.2%;P=0.143; IDI:5.8%;P=0.04). Conclusion. One-h PG at the time of remission is a better predictor of hyperglycemia relapse than traditional glycemic markers among obese Blacks presenting with DKA/SH. Testing 1-h PG at insulin discontinuation identifies individuals at high risk of developing hyperglycemia relapse.